The real crash : America's coming bankruptcy--how to save yourself and your country - Schiff, Peter D., 1963- (New York : St. Martin's Press, 2012)
Predicts a worse crash if key economic changes cannot be made, arguing that American consumer habits are at the heart of today's problems and recommends that the nation declare bankruptcy and rebuild broken systems from scratch.
Includes bibliographical references and index.
Keywords: Debts, Public -- United States; Saving and investment -- United States; Economic policy -- United States; Public debts -- United States; Saving and investment -- United States; United States -- Economic conditions -- 2009-; United States -- Economic policy -- 2009-; United States -- Economic conditions